Same tune, different song — cytokinins as virulence factors in plant–pathogen interactions?. (August 2018) - Spallek, Thomas; Gan, Pamela; Kadota, Yasuhiro; Shirasu, Ken
Graphical abstract: Highlights: Bacteria, fungi, nematodes and parasitic plants produce cytokinins. Cytokinins alter host susceptibility and disease symptoms. External factors modulate host sensitivity to cytokinins. Pathogen-produced cytokinins act beyond the infection site. Abstract : Virulence factors are molecules that enable plant pathogens to infect and colonize host tissues successfully. These molecules co-evolve with host genes to ensure functionality and to avoid recognition by the host immune system. Some pathogens also produce the plant growth hormone cytokinin (CK) and other plant hormones that contribute to virulence without being subjected to the molecular arms race. Here, we summarize recent findings regarding the role of CKs during infection and the establishment of plant diseases. We discuss commonalities and differences in CK biosynthesis, perception, and activity in infections by different phytopathogenic bacteria, fungi, nematodes and parasitic plants. Finally, we attempt to answer the question if CKs can be classified as bona fide virulence factors.